Pengembangan Aplikasi Website untuk Manajemen Bahan Pergudangan Berbasis Web - Rivky Kurniatama; Vina Ayumi (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
Efficient warehouse management is a critical factor in maintaining smooth business operations. However, many companies still use manual methods that are prone to errors and time-consuming. This research aims to design and implement a web-based warehouse management system application that simplifies stock management, records transactions of goods entering and leaving the warehouse, and provides real-time reporting. The research adapts the waterfall method, which includes requirements analysis, system design, implementation, deployment, and testing. This study analyzes the warehouse management issues at Sari Rasa Group as a case study. The application is developed using PHP programming language and MySQL database, with a responsive interface for easy access across various devices. Based on the analysis, the use case diagram in this system includes one actor, the admin. The admin can perform activities such as logging in, managing product data, managing request data, managing goods expenditure data, managing goods input data, and creating daily and monthly summaries. The warehouse management website application will be developed with six classes: user, product data, stock input, output data, stock output, and reports. The test results show that the application can assist in the process of recording goods in and out, enabling warehouse management to minimize user errors.